2011
DOI: 10.1080/17470218.2011.552729
|View full text |Cite
|
Sign up to set email alerts
|

Intake of High-Intensity Sweeteners Alters the Ability of Sweet Taste to Signal Caloric Consequences: Implications for the Learned Control of Energy and Body Weight Regulation

Abstract: Recent results from both human epidemiological and experimental studies with animals suggest that intake of non-caloric sweeteners may promote, rather than protect against, weight gain and other disturbances of energy regulation. However, without a viable mechanism to explain how consumption of non-caloric sweeteners can increase energy intake and body weight, the persuasiveness of such results has been limited. Using a rat model, the present research showed that intake of non-caloric sweeteners reduces the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 30 publications
(49 reference statements)
10
94
3
Order By: Relevance
“…Despite the long history of usage there continues to be considerable controversy concerning their role in the diet, particularly whether they are a useful tool as an aid in weight loss and weight loss maintenance (3)(4)(5)(6). NNS provide sweetness equivalent to NS but contribute essentially zero energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the long history of usage there continues to be considerable controversy concerning their role in the diet, particularly whether they are a useful tool as an aid in weight loss and weight loss maintenance (3)(4)(5)(6). NNS provide sweetness equivalent to NS but contribute essentially zero energy.…”
Section: Introductionmentioning
confidence: 99%
“…While it is plausible that the NNS participants were more likely to adhere to the dietary recommendations due to less hunger than the Water group we cannot conclude this based on this study. Some authors (3,5,6) have suggested that use of NNS may increase appetite for sweet foods and disrupt regulation of energy balance. Weight loss results for the present study suggest that NNS consumption did not increase energy intake from other foods compared to water.…”
mentioning
confidence: 99%
“…Possible mechanisms for the metabolic activity of NNS include altered ability to compensate for calories expected by sweet taste (Swithers et al 2009;Davidson et al 2011), alterations in the gut microbiota processing of nutrients (Palmnas et al 2014;Abou-Donia et al 2008;Suez et al 2014) and/or inhibition of intestinal alkaline phosphatase (Gul et al 2017). Neither the area under the glucose response curve nor the area under the insulin response curve was different between aspartame treatment or sucralose treatment compared with control in response to an oral glucose load.…”
Section: Discussionmentioning
confidence: 96%
“…Greater preferences are shown for novel flavors paired with sugar if animals have previously been exposed to artificial sweeteners (Davidson, Martin, Clark, & Swithers, 2011;Swithers, Ogden, Laboy, & Davidson, 2012). Additional work has shown that animals given artificial sweeteners not only show evidence of changes in learned responses, but that these effects translate into overeating, excess weight gain, and altered physiological responses (Davidson et al, 2011;Davidson & Swithers, 2004;Feijo et al, 2013;Mitsutomi et al, 2014;Swithers, Baker, & Davidson, 2009;Swithers & Davidson, 2008;Swithers, Laboy, Clark, Cooper, & Davidson, 2012;Swithers, Martin, Clark, Laboy, & Davidson, 2010;Swithers, Sample, & Davidson, 2013;Swithers, Sample, & Katz, 2013). Among the physiological alterations observed is a decrease in the release of the incretin hormone GLP-1 , which has been implicated in regulation of food intake, blood sugar levels and protection of the cardiovascular system (e.g.…”
Section: Mechanisms That Might Underlie Counterintuitive Consequencesmentioning
confidence: 96%